Rooting behaviour and soil properties in different bamboo species of Western Himalayan Foothills, India - R. Kaushal (Nature Portfolio, 2020)
Abstract Due to extensive root system, connected rhizome bamboos are considered suitable for improving soil properties within a short period, though most of the claims are anecdotal and need to be supported with quantified data. The study evaluates seven bamboo species viz., Bambusa balcooa, Bambusa bambos, Bambusa vulgaris, Bambusa nutans, Dendrocalamus hamiltonii, Dendrocalamus stocksii and Dendrocalamus strictus for their rooting pattern and impact on soil health properties. Coarse and fine root intensity was maximum in B. vulgaris. Coarse root biomass ranged from 0.6 kg m−3 in B. nutans to 2.0 kg m−3 in B. vulgaris and B. bambos. Fine root biomass ranged from 1.1 kg m−3 in B. nutans to 4.5 kg m−3 in D. hamiltonii. Contribution of fine roots in terms of intensity and biomass was much higher than coarse roots. Fine root biomass showed declining trend with increase in soil depth in all the species. During sixth year, the litter fall ranged from 8.1 Mg ha−1 in D. stocksii to 12.4 Mg ha−1 in D. hamiltonii. Among soil physical properties significant improvement were recorded in hydraulic conductivity, water stable aggregates and mean weight diameter. Soil pH, organic carbon and available phosphorus under different species did not reveal any significant changes, while significant reduction was observed in total nitrogen and potassium. Significant positive correlation was observed between WSA and iron content. Soil microbial population and enzyme activities were higher in control plot. Considering root distribution, biomass, soil hydraulic conductivity and water stable aggregates, B. bambos, B. vulgaris and D. hamiltonii are recommended for rehabilitation of degraded lands prone to soil erosion.